Behavior of Eradicating Mosquito Nests and Larva Index With Incidence Rate of Dengue Infection at Kupang City - de Fatima, Julio CA; Steven, Steven; Wihanto, Laura (JOURNAL OF WIDYA MEDIKA JUNIOR, 2020)
Introduction : Dengue infection occurs at a large scale in Indonesia, especially in Kupang City. The incidence rate of dengue infection in January 2019 was 245 cases and caused 15 deaths. The number of cases and mortality at Kupang City increased in 2019. In 2018, dengue infection attacked 210 persons, and one person died due the infection. Thus Kupang City was determined to have extraordinary incidents of dengue infection by the government. Aim : This research was conducted to determine whether there is a relationship between larvae index and the behavior of eradicating mosquito nest with the incidence of dengue infection in the city of Kupang. Method: This study used a cross-sectional design and data collection was carried out by random sampling with a total sample of 60 samples divided into three working areas of the health center and secondary data in the form of the incidence of dengue infections obtained from the health center in January-June 2019 period. Results: there was a significant relationship between the behavior of eradicating mosquito nest with the incidence rate of dengue infection in Kupang City (p=0,006). A significant correlation between larva existence with the incidence rate of dengue infection (p=0,006) and significant correlation between the behavior of eradicating mosquito with larva existence (p=0,000). Conclusion: there is a significant relationship between the behavior of eradicating mosquito nests and larva existence with the incidence rate of dengue infection at Kupang City.